1997
DOI: 10.2337/diacare.20.2.202
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Insulin Therapy and Normoglycemia: Effects on erythrocyte lipid peroxidation in NIDDM patients

Abstract: The observed erythrocyte LPO in NIDDM decreased after a short-term adaptive insulin therapy. This decrease could be principally attributed to the normalized glycemia that reduces reactive oxygen species (ROS) production, which in turn may explain the increase in erythrocyte membrane vitamin E and the decrease in MDA. This study shows the value of a euglycemic environment in NIDDM to reduce LPO and, at long range, to minimize clinical diabetes complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
23
0
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 0 publications
3
23
0
3
Order By: Relevance
“…**p < 0.0001; a: significantly different from baseline; b: significantly different from control. [49] and its concentration is elevated in poorly controlled type 2 diabetic patients [50]. The serum MDA concentrations in controls, which remained unaltered over the six month period was significantly higher than that of the managed exercise groups.…”
Section: Discussionmentioning
confidence: 88%
“…**p < 0.0001; a: significantly different from baseline; b: significantly different from control. [49] and its concentration is elevated in poorly controlled type 2 diabetic patients [50]. The serum MDA concentrations in controls, which remained unaltered over the six month period was significantly higher than that of the managed exercise groups.…”
Section: Discussionmentioning
confidence: 88%
“…34,35 In line with this notion, in type 2 diabetic patients the total plasma antioxidant capacity, erythrocyte lipid peroxidation activity, the susceptibility of LDL cholesterol to oxidation, 36 -38 and the excretion of oxidized products of arachidonic acid 15 are all increased, in proportion to the severity of hyperglycemia. 39,40 Even in nondiabetic subjects, the relative hyperglycemia induced by an oral glucose tolerance test stimulates the production of free radicals. 41 Furthermore, increased reactive oxygen species activity has been documented in hyperinsulinemic nonhyperglycemic conditions, such as obesity, 42 essential hypertension, 5 smoking, 3 and dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 The role of antioxidant defence mechanisms in diabetic patients is controversial. 19,23,[45][46][47][48][49] Matkovics et al 46 have shown an increased activity of membrane bound CAT in the erythrocytes from diabetics and Kedziora-Kornatowska et al 47 have shown decreased enzyme activity, while some others 48 could not detect any change in erythrocyte CAT activity in diabetics as compared to controls. We found a significant increase in the erythrocyte CAT activity in patients NIDDM with and without complications when compared to the controls.…”
Section: Discussionmentioning
confidence: 99%